Invers Matriks Ordo 3x3 Dengan Menggunakan Metode Operasi Baris Elementer (OBE) - Wulandari, Riska (Jurnal Pustaka Cendekia Pendidikan, 2024)
Matrix is ​​a branch of Linear Algebra, which is one of the important topics in mathematics. In line with the development of science, the application of matrices is often found in everyday life, both in the field of mathematics itself and for other disciplines. This use is widely used in solving problems related to everyday life, for example in banking applications, in the world of sports, and in the economic field. Whereas in mathematics, matrices can be used to handle linear models, such as finding solutions to systems of linear equations. On the other hand, there are also many problems that often arise related to the problem of the matrix itself, including how to determine the inverse of a matrix, which is also known as the inverse of a matrix. While the problem that often arises in finding the inverse matrix is ​​if the matrix is ​​neither square nor singular. In fact, a matrix is ​​said to have an inverse if and only if it is a square matrix and is non-singular. An interesting discussion in matrix theory is determining the inverse of a matrix. Inverses have an important role in solving several problems in matrices and are widely used in mathematics and applied sciences. Many methods are used in finding the inverse matrix including substitution, matrix partitioning, adjoining matrix, Gaussian elimination, Gauss-Jordan elimination, elementary row operations (OBE), elementary inverse matrix multiplication, and LU matrix decomposition. This article explains how to solve an inverse matrix of order 3x3 using elementary row operations (obe) method.